Husserl - Bell, David, 1947 April 24- (Arguments of the philosophers., 1999)
One of the most important and influential philosophers of the 20th century, up to now Edmund Husserl's influence has been restricted largely to the ""continental"" philosophical tradition. In this critical examination of Husserl's philosophy, David Bell introduces those who work in the broadly ""analytic"" tradition to the arguments and ideas of this fascinating thinker. Bell considers Husserl's philosophy as a whole, tracing its origins in Brentano's teachings, and the way it developed from the earliest writings on logic to the last works on culture and the ""Lebenswelt"". He also shows how H.